KNOWS: Kognitiv Networking Over White Spaces - Yuan, Yuan; Bahl, Victor; Chandra, Ranveer; Chou, Philip A.; Ferrell, Ian; Moscibroda, Thomas; Narlanka, Srihari; Wu, Yunnan (DySpan 2007: 2nd IEEE Symposium on Dynamic Spectrum Access Networks, Dublin, Ireland, 2007)
The Federal Communications Commission (FCC) has announced that it is willing to consider unlicensed operation in the TV broadcast bands. Compared to the ISM bands, this portion of the spectrum has several desirable properties for robust data communications. However, to make efficient use of this spectrum in a way that is non-disruptive to incumbents, there are a number of challenges that must be handled. For example, an unused portion of the spectrum must be found, and it is likely that its availability will vary over time. To address such challenges, we present KNOWS, a cognitive wireless networking system. KNOWS is a hardware-software platform that includes a spectrum-aware Medium Access Control (MAC) protocol and algorithms to deal with spectrum fragmentation.We describe our prototype and present evaluation results obtained from simulating our MAC protocol. We show that in common scenarios KNOWS accomplishes a remarkable 200% throughput improvement over systems that use a IEEE 802.11 based MAC protocol.